2022
DOI: 10.1002/ccr3.5373
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐existing singleton E138A mutations in the reverse transcriptase gene do not affect the efficacy of first‐line antiretroviral therapy regimens using rilpivirine in human immunodeficiency virus‐infected patients

Abstract: General consensus suggests that even singleton E138A mutations in HIV reverse transcriptase at baseline are associated with resistance to rilpivirine (RPV). We detected 11 pre‐existing E138A carriers treated with RPV in the pan European EuResist database. However, all 11 patients presented with full virological efficacy for first‐line RPV‐based ART regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…For example, Theys et al [ 29 ] observed that the emergence of K65R in the reverse transcriptase coding region was significantly favored in HIV-1 subtype C in PLWH being treated with tenofovir, suggesting subtype-specific pathways that facilitate the emergence of an otherwise-rare RAM. More recently, Kuznetsova et al [ 30 ] identified 11 individuals in the EuResist database harboring the reverse transcriptase natural polymorphism E138A who started a first-line ART including rilpivirine. Even though the variant E138A moderately decreases susceptibility to RPV in vitro and is included in the list of rilpivirine RAMs in several algorithms, treatment with RPV-based ART was fully effective in all 11 patients, supporting the effectiveness of RPV in first-line therapy in countries such as those belonging to the Russian Federation, where the natural polymorphism E138A is present in 4–8% of circulating strains.…”
Section: Findings To Datementioning
confidence: 99%
“…For example, Theys et al [ 29 ] observed that the emergence of K65R in the reverse transcriptase coding region was significantly favored in HIV-1 subtype C in PLWH being treated with tenofovir, suggesting subtype-specific pathways that facilitate the emergence of an otherwise-rare RAM. More recently, Kuznetsova et al [ 30 ] identified 11 individuals in the EuResist database harboring the reverse transcriptase natural polymorphism E138A who started a first-line ART including rilpivirine. Even though the variant E138A moderately decreases susceptibility to RPV in vitro and is included in the list of rilpivirine RAMs in several algorithms, treatment with RPV-based ART was fully effective in all 11 patients, supporting the effectiveness of RPV in first-line therapy in countries such as those belonging to the Russian Federation, where the natural polymorphism E138A is present in 4–8% of circulating strains.…”
Section: Findings To Datementioning
confidence: 99%
“…We found it in 5.8% of the patients with an association with sub-subtype A6, which is in line with earlier report in sub-subtype A6, where the frequency was 4–8% depending on the region [ 38 ]. It has recently been reported that this singleton mutation, before starting treatment with RPV, may not affect the efficacy of the ART [ 43 ]. In the protease ORF, the L33F (0.7%) polymorphism was found, which is similar to the frequency observed in other subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Another polymorphic mutation in sub-subtype A6 E138A (5.3%) was the most common NNRTI mutation detected in treatment-naïve Russian patients. In vitro data from site-directed mutagenesis showed that E138A causes a two-fold reduction in susceptibility to RPV [43,44]; however, this does not appear to affect the effectiveness of RPV-containing treatment in real practice [45,46].…”
Section: Discussionmentioning
confidence: 97%
“…In 2021, the percentage of PLWH who achieved an undetectable HIV viral load (VL) was 46.4%, and it was 79.9% among those receiving ART [10]. It has been shown that achieving the third target of "95-95-95" for viral suppression is key to reducing the rate of new HIV infections [12].…”
Section: Introductionmentioning
confidence: 99%